P255 Defining the distinct role of a modern complex polyp multidisciplinary meeting; first preliminary audit. (19th June 2022) - Zeidan, Shady; Elkady, Soad; Gatopoulos, Polychronis; Spinner, James; Gamble, Simona; Muller, Andrew; Mangam, Sudhakar; Hills, Katherine; Sebastian, Joseph; Tsiamoulos, Zacharias
Abstract : Introduction: The Complex Polyp Multidisciplinary Meeting (CP-MDM) is a well-established service in our trust since 2018. It is governed by a Standard Operation Policy (SOP) with clearly defined referral criteria and pathways. Assigning appropriate diagnostic and therapeutic pathway has an impact on the endoscopy and cancer services of the trust as well as patients' outcomes. Methods: The weekly CP-MDM has a core membership of 2 gastroenterologists, 2 surgeons, a pathologist, CP fellow, CP specialist nurse, bowel cancer screening (BSC) nurse, co-ordinator and service booking manager. Referrals are typically made after a diagnostic colonoscopy booked via BCS, cancer pathway clinics/post Colorectal Cancer MDM discussion and routine clinics. Polyp characteristics, from photos, endoscopy reports and biopsy results, alongside patient physical performance and co-morbidities are reviewed to reach a consensus. When indicated, imaging are also reviewed by a radiologist. The urgency of the therapeutic procedure is downgraded/upgraded according to agreed pathways. We collected data on all patients referred to the CP-MDM between July 2020 and January 2022. Source of referral, meeting outcomes and final pathway were obtained from electronic patients records and endoscopy report. Results: Over the 19 months period, 756 cases were discussed. Sources of referral were Bowel Cancer Screening/BCS 163 (21%), Cancer Pathway (2week/C-MDM)- 445 (58%), routine clinics 113 (14.9%) and 35 (4.6%), data are missing. After the first discussion nearly third of the patients (237, 31%) were discharged and/or downgraded. 120 (16%) patients required a second discussion and only 45 (6%) required second diagnostic endoscopy to reach a final outcome. Therapeutic endoscopy was agreed for 368 (48%) patients. Within this group, the urgency of the procedure was upgraded for 19 out of 50 (38%) routine referrals. Using a designated streaming or priority tool (based on guidelines and SOP policy) for triaging, 123 (out of 256, 48%) cancer pathway patients were downgraded to the routine pathway whereas one BCS patient out of 52 (2%) was downgraded. Conclusions: A well-established and busy CP-MDM service, which could attract more regional referrals. CP-MDM appeared to downgrade nearly 50% of cancer pathway patients who have benign but complex polyps. Further analysis and alignment of the proposed management plan with final outcomes within CP-MDM are warranted alongside a health economics examination of the service.